Comparison of mHTT Antibodies in Huntington's Disease Mouse Models Reveal Specific Binding Profiles and Steady-State Ubiquitin Levels with Disease Development. - Zubeyde Bayram-Weston; Lesley Jones; Stephen B Dunnett; Simon P Brooks (PLoS ONE, 2016)
Huntington's disease (HD) cellular pathology is characterised by the aggregation of mutant huntingtin (mHTT) protein into inclusion bodies. The present paper compared the sensitivity of five widely used mHTT antibodies (S830; MW8; EM48; 1C2; ubiquitin) against mice from five commonly used HD mouse models (R6/1; YAC128; HdhQ92; B6 HdhQ150; B6 x129/Ola HdhQ150) at two ages to determine: the most sensitive antibodies for each model; whether mHTT antibody binding differed depending on aggregation stage (diffuse versus frank inclusion); the role of ubiquitin during aggregation as the ubiquitin proteosome system has been implicated in disease development. The models demonstrated unique profiles of antibody binding even when the models varied only by background strain (HdhQ150). MW8 was highly sensitive for detecting frank inclusions in all lines whereas EM48, ubiquitin and 1C2 demonstrated consistent staining in all models irrespective of age or form of mHTT. MW8 and S830 were the most sensitive antibodies with 1C2 the least. Ubiquitin levels were stable for each model regardless of age. Ubiquitin was particularly sensitive in young YAC128 mice that demonstrate an absence of inclusions until ~12 months of age suggesting high affinity to mHTT in its diffuse form. The data indicate that generalisations across models regarding the quantification of aggregations may not be valid and that mHTT antibody binding is unique to the mouse model and sensitive to changes in inclusion development.